Acoustic field in the mechanical workshop - Janusz Piechowicz (Archives of Acoustics)
Either wave methods or geometric ones are used to describe an acoustic field in industrial halls. The acoustic field distribution in such halls is not uniform, thus the assumption of field diffusivity applied in an acoustics of interiors is often not fulfilled. The room forms amplitude and phase characteristics of the signal, introducing additionally effects related to space development, which are decisive for the acoustic pattern in the observation point. The paper presents an analysis of an acoustic field inside an industrial room, when one machine of not large dimensions is operating. The geometric model of the workshop was implemented and Raynoise software was used to determine the distribution of the sound level for selected frequencies. The measurement results and computer simulations related to the acoustic field distribution are given.